Lassa virus RNA detection from suspected cases in Nigeria, 2011-2017 - Babalola, Salu Olumuyiwa (Pan Afr Med J, 2019)
INTRODUCTION: The diagnosis of Lassa fever is crucial to confirm cases, as well as to control/prevent nosocomial and community-based transmission and initiation of treatment, which is still limited in the country. Thus, we aimed at providing some information on the laboratory detection of Lassa from suspected cases in Nigeria. METHODS: This was a retrospective study of seasonal Lassa fever outbreaks data from 1,263 samples analyzed using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) at the Virology Research Laboratory, College of Medicine, University of Lagos/Lagos University Teaching Hospital between year 2011 and 2017. Data were analyzed using the 21(st) edition of SPSS statistical software (2015). RESULTS: The RT-PCR test confirmed the presence of Lassa in 112 (8.9%) comprising 61 (54.4%) males, 48 (42.9%) females and 3 (2.7%) individuals without gender information. Those aged between 18 and 49 years were mostly affected. There was a decline in the detection of Lassa from 4.7% in 2011/2012 to less than 1% by the 2014/2015. However, during the 2015/2016 and 2016/2017 seasons the detection rates increased to 10.4% and 15.1% respectively. The Northern region of Nigeria reported high confirmed cases of Lassa. The South Western region also witnessed an increased Lassa fever positivity rate of 13.4% of which Lagos and Ogun states being the focal state of Lassa activity in the region. CONCLUSION: These established the need for heightening the continued surveillance for Lassa as well as the establishment of other testing facilities within these endemic regions for prompt diagnosis of Lassa fever.